Renal Tubular Acidosis and Hypokalemic Paralysis as a First Presentation of Primary Sjögren’s Syndrome - Arun Sedhain; Kiran Acharya; Alok Sharma; Amir Khan; Shital Adhikari (Case Reports in Nephrology)
Sjögren’s syndrome is an autoimmune disease with multisystem involvement and varying clinical presentation. We report the clinical course and outcome of a case who presented with repeated episodes of hypokalemia mimicking hypokalemic periodic paralysis and metabolic acidosis, which was later diagnosed as distal renal tubular acidosis secondary to primary Sjögren’s syndrome. A 50-year-old lady, who was previously diagnosed as hypokalemic periodic paralysis, presented with generalized weakness and fatigue. She was found to have severe hypokalemia with normal anion-gap metabolic acidosis consistent with distal renal tubular acidosis. Subsequent evaluation revealed Sjögren’s syndrome as the cause of her problems. Kidney biopsy done to evaluate significant proteinuria revealed nonproliferative morphology with patchy acute tubular injury and significant chronic interstitial nephritis. The patient responded well to potassium supplementation and oral prednisolone. Presentation of this case highlights the necessity of close vigilance while managing a case of repeated hypokalemia, which could be one of the rare clinical manifestations of Sjögren’s syndrome.